Migration of Young Indonesian Workers to Australia: Opportunities, Challenges, and an Inclusive Perspective - Chazie Mugan Virgine Diaz; Ilmi Dwiastuti; Uchaimid Biridlo’i Robby (Journal of Public Policy, Governance and Local Government, 2026)
This article discusses the phenomenon of young Indonesian migrant workers to Australia in the context of opportunities, challenges, and an inclusive perspective. The main focus is on how bilateral cooperation between Indonesia and Australia, such as the Colombo Plan Scholarship (CSP) program and the Work and Holiday visa, opens up mobility access for the younger generation to gain work experience and skill enhancement. On the other hand, this phenomenon also poses challenges in the form of potential brain drain, particularly among scholarship recipients who choose to settle and pursue careers in Australia after completing their studies or work period. This study employs a qualitative approach with secondary data analysis from various academic and policy sources. The findings indicate that the diplomatic momentum during the 2024–2026 period provides significant opportunities for skilled Indonesian workers to develop in the global market. Nevertheless, wage gaps, work environment quality, and limited career ecosystems domestically serve as the primary driving factors for workforce retention in Australia. This has the potential to reduce the contribution of superior human resources to national development. In addition, the article highlights the importance of an inclusive perspective, particularly for youth with disabilities, who still face limitations in accessing international mobility programs. Therefore, strategic policies are needed, such as expanding the Mutual Recognition Arrangement (MRA) and strengthening disability inclusion programs, to ensure that the benefits of migration can be felt more equitably while mitigating the negative impacts of brain drain.